Students’ Contextual Ability: Basis for Developing the Multimodal Filipino Aptitude Test (MFAT) - Sabuga-a, Jaspher Kim (International Journal of Arts, Sciences and Education, 2025)
The test is not merely a measure of knowledge but a step toward more effective learning. Through the Multimodal Filipino Aptitude Test (MFAT), we gain a deeper understanding of students’ contextual reading abilities across various text types. This study aims to develop and validate the Multimodal Filipino Aptitude Test (MFAT) to assess the contextual reading skills of Grade 7 students in the Tampakan district. A test-retest design was used with 159 students from three public high schools to determine the instrument’s reliability. Data were gathered using multimodal assessments involving written, visual, and multimodal texts. Results showed that students demonstrated a moderate level of comprehension across all text types. The MFAT was also proven to be a reliable and valid assessment tool. Continued refinement of the assessment is recommended to better address students’ needs and improve teaching strategies. Keywords: multimodal filipino aptitude test, contextual ability, multimodal assessment, comprehension skills